Inflammatory and tumor-like lesions of the pancreas: Review - Luchini, Claudio; Fassan, Matteo; Doglioni, Claudio; Capelli, Paola; Ingravallo, Giuseppe; Renzulli, Giuseppina; Pecori, Sara; Paolino, Gaetano; Florena, Ada Maria; Scarpa, Aldo; Zamboni, Giuseppe (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
Inflammatory/tumor-like lesions of the pancreas represent a heterogeneous group of diseases that can variably involve the pancreatic gland determining different signs and symptoms. In the category of inflammatory/tumor-like lesions of the pancreas, the most important entities are represented by chronic pancreatitis, which includes alcoholic, obstructive and hereditary pancreatitis, paraduodenal (groove) pancreatitis, autoimmune pancreatitis, lymphoepithelial cyst, pancreatic hamartoma and intrapancreatic accessory spleen. An in-depth knowledge of such diseases is essential, since they can cause severe morbidity and may represent a potential life-threatening risk for patients. Furthermore, in some cases the differential diagnosis with malignant tumors may be challenging. Herein we provide a general overview of all these categories, with the specific aim of highlighting their most important clinic-pathological hallmarks to be used in routine diagnostic activities and clinical practice.